2015
DOI: 10.1016/j.dt.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of magnetically impelled arc butt welded T11 tubes for high pressure applications

Abstract: Magnetically impelled arc butt (MIAB) welding is a pressure welding process used for joining of pipes and tubes with an external magnetic field affecting arc rotation along the tube circumference. In this work, MIAB welding of low alloy steel (T11) tubes were carried out to study the microstructural changes occurring in thermo-mechanically affected zone (TMAZ). To qualify the process for the welding applications where pressure could be up to 300 bar, the MIAB welds are studied with variations of arc current an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Similar researches were conducted by Sivasankari et al. 79 to study the effect of upset current on the final strength and microstructure of the welded joints. Their research revealed that samples welded using higher upset current even with large variation of other welding parameters exhibit high weld strength and ductility due to the formation of acicular ferrite.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Similar researches were conducted by Sivasankari et al. 79 to study the effect of upset current on the final strength and microstructure of the welded joints. Their research revealed that samples welded using higher upset current even with large variation of other welding parameters exhibit high weld strength and ductility due to the formation of acicular ferrite.…”
Section: Introductionmentioning
confidence: 55%
“…Comparison of the metallography results with the simulation results for each phase distribution makes it clear that there is an absolutely good agreement between them and also the results that were reported by other researchers. 7,30
Figure 6.Distribution of phase content and microstructure of welded joints after cooling: (a) bainite; (b) pearlite; (c) ferrite; (d) microstructure of the weld line; (e) microstructure of transition zone – HAZ; (f) base material microstructure.
…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic flux density is identified as one of the main factors that affect the arc rotation behaviour in MIAB welding. The arc dynamics during the welding sequence control the uniformity and intensity of the heating at the weld surface [10]. The heated and plasticized weld surfaces are forged together at a preset time to form the weld.…”
Section: Significance Of Magnetic Field In Miab Weldingmentioning
confidence: 99%
“…Arc velocity varies in different phases of the MIAB welding process. The heating stage experiences unstable arc velocity [5] and may lead to the quenching of the arc by forming a short circuit between the tube faces. These complications are prominent with larger thickness tubes and thus describe the limitations of this process for application to tubes of thickness larger than 8mm [3] which have restricted its wide adaptability in the manufacturing industry.…”
Section: Fig 1 Arc Impelling Mechanism In Miab Weldingmentioning
confidence: 99%